logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
0 votes

Prove the rule of exponents $(ab)^n=a^nb^n$ by using principle of mathematical induction for every natural number.

Can you answer this question?
 
 

1 Answer

0 votes
Let $P(n)$ be the given statement
i.e., $P(n) : (ab)^n=a^nb^n$
We note that $P(n)$ is true for $n=1$ since $(ab)^1=a^1b^1$.
Let $P(k)$ be true, i.e.,
$\qquad (ab)^k=a^kb^k$----------(1)
We shall now prove that $P(k+1)$ is true whenever $P(k)$ is true.
Now, we have
$\qquad = (ab)^{k+1} =(ab)^k(ab)$
$ \qquad = (a^kb^k) (ab)\qquad$ [ by (1) ]
$ \qquad = (a^k.a^1) (b^k.b^1)=a^{k+1}.b^{k+1}$
Therefore, $P(k+1)$ is also true whenever $P(k)$ is true. Hence by principle of mathematical induction, $P(n)$ is true for all $n \in N$.
answered May 5, 2014 by thanvigandhi_1
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...